Study of the Protection of Aluminum Alloy Surfaces by a Graphene-Modified Fluorocarbon Anticorrosive Coating - Peng Wang; Dayong Cai (International Journal of Photoenergy)
Graphene-modified anticorrosion coatings have become a hot spot in the field of metal protection due to the large-scale promotion of aluminum alloys, which are prone to corrosion in marine and atmospheric environments. The protection of aluminum alloy surfaces by a graphene-modified anticorrosive coating was explored in this study by applying a graphene-modified anticorrosive coating to an aluminum alloy surface to test its resistance to corrosion. Dispersion-treated reduced graphene oxide (rGO) was used to modify the epoxy resin and fluorocarbon resin. It was found, by using a scanning electron microscopy (SEM) and the microstructure of the coating made by the Raman Spectroscopy Institute, that the addition of rGO could effectively improve the porosity of the epoxy primer, and the electrochemical workstation was able to resist the graphene-modified anticorrosive coating. The corrosion performance was quickly characterized, the polarization curve and the AC impedance curve were fitted, and it was found that the self-corrosion current density (Jcorr) of the graphene-modified anticorrosive coating was the smallest (1.190×10−7 A/cm2) when 0.6% of rGO was added; the impedance modulus (∣Z∣) was the largest (104), the capacitive reactance arc radius was the largest, and the coating resistance was the largest after fitting (15517 Ω). When 0.8% of rGO was added, the dispersion coefficient was large, and it had a good physical insulation performance. The main reason for the reduction of the corrosion resistance was that the agglomeration of rGO made the aluminum alloy matrix and the external corrosive environment form a highly conductive circuit, thereby accelerating the corrosion of the aluminum alloy matrix.